Tobacco Use and Associated Factors Among Men in Tanzania: Further Analysis of the 2022 Tanzania Demographic and Health Survey Data - Christopher Hariri Mbotwa; Linus Paul Rweyemamu (SAGE Publishing, 2024)
Background: Tobacco use is a significant public health challenge, contributing to preventable diseases and premature deaths globally. We aimed to determine the prevalence of tobacco use and associated factors among men in Tanzania. Methods: This was a cross-sectional analysis of data from the 2022 Tanzania Demographic and Health Survey and Malaria Indicator Survey. The study population comprised men aged 15-49 years. Weighted logistic regression was performed to identify factors associated with tobacco use. Results:  A total of 5763 men with a mean age of 28.6 ± 10 years were included in the analysis. The overall prevalence of tobacco use was 11.1%, with 95% of users consuming smoked products, 17.1% using smokeless products, and 12.1% using both smoked and smokeless products. Older age was associated with increased odds of tobacco use, with odds of tobacco use increasing with each higher age group. Similarly, alcohol consumption was associated with greater odds of tobacco use. On the other hand, having a secondary education or higher, lack of occupation, being the head of the household, and owning a mobile telephone were associated with lower odds of tobacco use. Geographically, men from the Eastern zone and Zanzibar exhibited greater odds of tobacco use, while those from the Southern highlands zone had lower odds. Conclusion: This study revealed a significant prevalence of tobacco use among Tanzanian men and was associated with different individual, interpersonal, and community factors. The findings underscore the need for targeted interventions considering age-specific risk factors and geographical variations.